2014
DOI: 10.1186/1471-2164-15-753
|View full text |Cite
|
Sign up to set email alerts
|

Functional gene arrays-based analysis of fecal microbiomes in patients with liver cirrhosis

Abstract: BackgroundHuman gut microbiota plays an important role in the pathogenesis of cirrhosis complications. Although the phylogenetic diversity of intestinal microbiota in patients with liver cirrhosis has been examined in several studies, little is known about their functional composition and structure.ResultsTo characterize the functional gene diversity of the gut microbiome in cirrhotic patients, we recruited a total of 42 individuals, 12 alcoholic cirrhosis patients, 18 hepatitis B virus (HBV)-related cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 49 publications
(53 reference statements)
3
23
0
Order By: Relevance
“…Cirrhosis is associated with profound changes in the gut microbiota as compared to healthy controls . This ‘dysbiosis’ progresses as the liver disease evolves to advanced stages and is characterized by a reduced bacterial diversity and shifts in community structure and composition .…”
Section: Introductionsupporting
confidence: 90%
“…Cirrhosis is associated with profound changes in the gut microbiota as compared to healthy controls . This ‘dysbiosis’ progresses as the liver disease evolves to advanced stages and is characterized by a reduced bacterial diversity and shifts in community structure and composition .…”
Section: Introductionsupporting
confidence: 90%
“…Fecal samples were collected from 15 compensated cirrhotic patients and 15 age-matched controls to evaluate changes in stool microbiota composition and function in cirrhotic patients after omeprazole therapy, and they found that omeprazole was associated with a microbiota shift and functional change in the distal gut in compensated cirrhotic patients that could set the stage for bacterial overgrowth (Bajaj et al, 2014). Chen et al (2014) researched on fecal samples from 12 alcoholic cirrhosis patients, 18 hepatitis B virus related cirrhosis patients, and 12 normal controls using a specific functional gene array, which suggested that the functional composition of fecal microbiota was heavily influenced by cirrhosis, especially by alcoholic cirrhosis. Grąt et al (2014) confirmed the enrichment of lactobacilli in the gut microflora of liver transplant candidates with cirrhosis as revealed by intestinal flora component analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Chassaing et al also suggest that mechanisms by which HBV promotes liver disease is mediated, in part, via the gut microbiota [63]. Constantly, functional gene arrays data showed that the abundance of functional genes relevant to nutrient metabolism, including amino acid metabolism, lipid metabolism, nucleotide metabolism, and isoprenoid biosynthesis, were significantly decreased in both the alcoholic cirrhosis group and the HBV-related cirrhosis group compared to normal controls [64]. These studies suggested that antibiotics could influence the gut microbiota and its related liver immunity.…”
Section: Gut Microbiota and Liver Injurymentioning
confidence: 91%